Creating brand of tourist territories as an element of multidimensional structure of the development of entrance tourism - Wahap, H.; Sadykbek, G.; Aetov, S.; Maulen, A. (BUKETOV BUSINESS REVIEW, 2017)
The article analyzes the structure of the brand of tourist territories, which is important for travelers when selecting a tourist zones and appears as a set of associations. The structure of the brand is explained by two main concepts as brand identity and brand image. Analyzed the relationship between them. Also, considered the concept of brand positioning, which is a specific mediator between the two. In its turn discussed the structure of brand identity. Also described the positive results of the formation of the brand for the tourist zones. The authors investigated a number of associations that are updated when a tourist thinks of the tourist zone and compares it with others. Shown the attributes that affect the image of the tourist area. As an example, presented the tourism branding Indian policy called «Incredible India». Summing up the results proved that the creating brand of tourist territories is a multidimensional structure.